2021
DOI: 10.1021/acs.jpcc.1c03597
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Gallium Sulfide Nanoflakes for UV-Selective Photoelectrochemical-type Photodetectors

Abstract: Two-dimensional (2D) transition-metal monochalcogenides have been recently predicted to be potential photo(electro)catalysts for water splitting and photoelectrochemical (PEC) reactions. Differently from the most established InSe, GaSe, GeSe, and many other monochalcogenides, bulk GaS has a large band gap of ∼2.5 eV, which increases up to more than 3.0 eV with decreasing its thickness due to quantum confinement effects. Therefore, 2D GaS fills the void between 2D small-band-gap semiconductors and insulators, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 129 publications
3
51
0
Order By: Relevance
“…It is worth noting that the R value of electrochemical intercalation ultrathin InSe (A-InSe) is 3 orders of magnitude higher than that of liquid-exfoliated few-layer InSe, which could be attributed to the better crystalline quality of electrochemical intercalation ultrathin InSe. Furthermore, the R values of A-InSe PEC photodetector not only are better than those of most 2D material-based self-powered PEC-type photodetectors in SI Table S6, but also are comparable to those of 2D InSe-based vdWHs self-powered photodetectors as shown in SI Table S7. ,, Compared with vdWHs devices, PEC devices have a simple device structure and facile fabrication process. Furthermore, the A-InSe PEC photodetectors show good reproducibility with small deviation for different devices as shown in Figure b–d and SI Tables S2–S4.…”
Section: Resultsmentioning
confidence: 91%
“…It is worth noting that the R value of electrochemical intercalation ultrathin InSe (A-InSe) is 3 orders of magnitude higher than that of liquid-exfoliated few-layer InSe, which could be attributed to the better crystalline quality of electrochemical intercalation ultrathin InSe. Furthermore, the R values of A-InSe PEC photodetector not only are better than those of most 2D material-based self-powered PEC-type photodetectors in SI Table S6, but also are comparable to those of 2D InSe-based vdWHs self-powered photodetectors as shown in SI Table S7. ,, Compared with vdWHs devices, PEC devices have a simple device structure and facile fabrication process. Furthermore, the A-InSe PEC photodetectors show good reproducibility with small deviation for different devices as shown in Figure b–d and SI Tables S2–S4.…”
Section: Resultsmentioning
confidence: 91%
“…[170][171][172][173] In addition, 2D materials, such as Bi 2 Te 3 , Sb 2 Te 3 , Bi 2 Se 3 , SnTe, and even graphene, can display unique symmetry-protected helical metallic edge states with an insulating interior, yielding so-called topological insulators. 174,175 As for graphene, research on other GRMs, including TMDs, 176,177 TMMs, [178][179][180][181] transition metal oxides (TMOs), 182 monoelemental 2D materials (silicene, phosphorene, germanene, stanene, borophene, gallenene, arsenene, antimonene, bismuthene, plumbene, selenene, and tellurene), 183,184 and MXenes, 185 have provided evidences that the band structure of such materials drastically changes as they shrink from the bulk to the monolayer due to quantum confinement effects. 170,171,186 The abundance of GRMs and the ability to stack them in a layer-by-layer manner in desired sequences, eventually through solutionprocessed methods, offer the possibility to create novel threedimensional (3D) architectures with entirely new functions, 187,188 which have been foreseen to design the next generation of PV devices.…”
Section: Chem Soc Revmentioning
confidence: 99%
“…The flexible PEC-type photo detectors coated with 2D UWBG semiconductor materials were recently fabricated to realize an effective photodetection under ultraviolet wavelength. [223][224][225][226] Bonaccorso and co-workers reported that GaSe-based PEC-type photodetectors (Figure 11a) exhibited a self-power capability and high responsivity. [227] As shown in Figure 11b, the responsivity of about 0.16 A W −1 was kept when increases to the light intensity the tested values of 57.6 µW cm −2 .…”
Section: Photoelectrochemical-type Photodetectormentioning
confidence: 99%